Meckel Gruber Syndrome- A Case Report And Review of Literature - Sümeyra Nergiz; Selda Demircan Sezer; Sündüz Özlem Altınkaya; Mert Küçük; Hasan Yüksel (Gynecology Obstetrics & Reproductive Medicine)
Meckel-Gruber syndrome (MGS) is a lethal autosomal recessive disorder. MGS is thought to be caused by ciliary dysfunction. The worldwide incidence of MGS varies from 1 in 13 250 to 1 in 140.000 live births. MGS is characterized by three main symptoms: central nervous system (CNS) malformations, tetramelic postaxial polydactyly and cystic renal dysplasia with associated fibrocystic changes of the liver, pancreas and epididymis. Here a case of MG syndrome, diagnosed in early weeks of gestation was reported.